Right ventricular diastolic function in patients with lung diseases in the absence or presence of pulmonary hypertension - A N Sumin; O G Arkhipov (Терапевтический архив, 2017)
Aim. To investigate the indicators of filling of the right ventricle (RV) in patients with chronic lung diseases with and without pulmonary hypertension (PH) compared to healthy individuals. Subjects and methods. 365 people (198 men); mean age 64.6±8.0 years) were examined and divided into a group of patients with respiratory pathology without and with PH (n=124 and n=138, respectively) and a comparison group that included individuals without cardiovascular and respiratory diseases (n=103). All underwent echocardiography with examination of RV filling flows (Et, At, Et/At), data of the spectral tissue Doppler imaging of the fibrous ring of the tricuspid valve (e’t, a’t, e’t/a’t), and early tricuspid flow propagation velocity (ETFPV). Results. All the groups were found to have an e’t/a’t decrease to 0.75 (0.63—0.90) — 0.8 (0.63—1.0; p=0.26). The groups showed no noticeable differences in indicators, such as Еt/Аt, e’t/a’t, and Еt/e’t ratios, although the increased size of the right heart was noted in patients without PH along with the ETFPV decrease from 33.5 (28—39) to 31.5 (24.5—36) cm/sec, which continued to substantially decline to 27.1 (24—35) cm/sec in patients with PH (p